The Power of Communicating the Family Firm Status The Positive Effect of Family Firms as a Brand on Consumer Buying Behavior and Consumer Happiness - Rosina, Margarete (Familienunternehmen und KMU,, 2018)
Margarete Rosina investigates whether it makes sense for family firms to communicate their family firm status to consumers. To do so, she conducts two experimental studies using a sample of 349 consumers. Using a branding perspective, the first study looks at whether consumers perceive family firm brands as more authentic and why and how this influences their buying behavior. The second study applies a consumer happiness perspective and investigates whether family firms signal prosocial behaviors related to "doing good", namely being a good employer and socially responsible, and whether this, in turn, leads to higher levels of consumer happiness when buying from family firms. Both studies indicate that the family firm status can be of strategic value for family firms. Contents Research on Marketing in Family Firms The Power of a Family Firm Brand: An Experiment in How Communicating the Family Status Affects Consumer Brand Choice and Willingness to Pay Family Firms and Consumer Happiness: Are Consumers of Family Firm Products Happier than Consumers of Non-Family Firm Products? Target Groups Researchers and students in the fields of management, strategy, branding, marketing and family firm research Practitioners in the areas of family firms, marketing, branding, corporate/business development and strategy The Author Dr. Margarete Rosina wrote her dissertation under the supervision of Prof. Dr. Andreas Hack at the Witten Institute for Family Business (WIFU) at Witten/Herdecke University.